Financial feasibility evaluation of BSF maggot cultivation at Bumi Farm, Cipaku Village, Bogor City - Dwi Meyliani Riswanti; Adi Surya Panji Gumilang (Jurnal Mantik, 2026)
The problem of food waste management, which continues to increase and dominate the composition of waste, necessitates circular economy-based solutions that not only solve the problem of waste accumulation but also provide economic benefits. One such solution is the cultivation of Black Soldier Fly (BSF) maggots, as maggots can reduce food waste by 90%. One of the businesses that cultivates BSF maggots is Bumi Farm, but since its establishment in 2020, no financial feasibility evaluation has been conducted. Therefore, this study aims to evaluate the financial feasibility of BSF maggot cultivation at Bumi Farm using NPV, IRR, PP, and Net B/C. The results of this study indicate that the BSF maggot cultivation business at Bumi Farm shows the following values NPV with a Bi Rate of 5.75% is IDR 152,700,000, which is considered feasible because the NPV value is > 0; IRR value of 36.71% is considered feasible because the IRR value is > Bi Rate; The Payback Period of 2 years and 10 months is feasible because the PP value is < Economic Life, and the Net B/C of 2.32 is feasible because the Net B/C value is > 1. The results of the analysis show that all financial feasibility indicators are met, so that the BSF Maggot Cultivation business at Bumi Farm is feasible to run because it meets all financial feasibility indicators